Sistem SCADA pada miniatur Smart Home Bertenaga Surya - Alfa Z Fikri, Mohammad; Sakhalish Zayyan, Muhammad; Edo Mikrado, Juan; B Sulistiawati, Irrine; Soetedjo, Aryuanto; Somawirata, I Komang; Sotyohadi , Sotyohadi (Jurnal FORTECH, 2022)
A smart home is a combination of technology and services in the home environment that aims to increase the efficiency, comfort and safety of its residents. This smart home is controlled by Outseal PLC which communicates locally using RS485 with Haiwell SCADA HMI. Apart from controlling and monitoring through the Haiwell SCADA HMI[1], you can do it via a smartphone by downloading the Haiwell Cloud app in the Playstore. When the light is turned on via the Haiwell Scada HMI or using a Smartphone, the buttons on the Haiwell Scada HMI and the smartphone will turn on. And there is a delay of about 5 seconds, due to the time it takes to send information to Outseal PLC. The main objective of this journal is to introduce children to smart home by making a miniature smart home using SCADA, Outseal PLC Arduino Mega and other components. In this paper we use SCADA, the RS 485 control protocol to create this miniature smart home. It used to be that if the user wanted to control equipment, he had to move near the wall and control the sacred. This method is inconvenient for the elderly and disabled. therefore created a smart home that can be controlled and controlled remotely This miniature smart home uses solar panels as an energy source so when there is a blackout, this miniature can still be used[2].